Pharmacists’ Knowledge, Attitudes, and Practices Regarding Nano-Pharmaceutical Availability in Hospitals - Abdulrahman Mahmood; Fidan Fikrat Ahmed (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
The medical application of nanomaterials with dimensions extending below 100 nm defines nanomedicine. The discipline provides solutions to multiple existing barriers in medical diagnosis and treatment management. Nanopharmaceutical knowledge from pharmacists will increase drug availability in the market while enhancing patient compliance to medication protocols. The research aimed to determine if nano pharmaceutical medications existed in Sulaymaniyah hospitals while evaluating pharmacist knowledge about these medications. This study used a questionnaire with a cross-sectional design to determine the availability of nanopharmaceutical medicines. It also examines knowing these nanopharmaceutical drugs among pharmacists based on questionnaires from previous studies on pharmaceutical formulations and nanoformulations. In addition, it tests the variables by Prism—GraphPad. The study collected one hundred surveys from pharmacists of many hospitals in the Sulaymaniyah city in Iraq. According to the findings, twelve are available in hospitals, with different frequencies with Rapamune being number one, with a 72% availability rate. Furthermore, the respondents showed that they know more about pharmaceutical formulations than nano-formulations. There were no enough nano-pharmaceutical drugs in Sulaimaniyah hospitals because there are no diverse nano-pharmaceutical formulations. Nanopharmaceuticals should be better understood by pharmacists by including nanomedicine courses in undergraduate pharmacy curricula.